2015
DOI: 10.1007/s11431-015-5904-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of laser geometric morphology type on SiC surface wettability

Abstract: To obtain effective surface morphology to control surface wettability, this work investigated the influence of protuberant and concave morphology, which are respectively represented by circle-dimpled and micro-square-convex morphology, on surface wettability. The geometric morphologies were processed on silicon carbide (SiC) surfaces by a laser-marking machine, and surface wettability was monitored by the measurement of contact angles using the sessile drop method. Correlation analysis between contact angles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…On the other hand, some surface processing methods are hot working ways, such as laser processing, in which melting and recrystallisation will be produced owing to the high temperature during the process. Kietziga et al [18] reported that the femtosecond-lasered sample showed superhydrophilicity after processing and varied to hydrophobic when the sample was exposed to air, which was also observed in our experiment [19]. Therefore, the processing method should be considered in the wetting behaviors transformation study of sealing surfaces.…”
Section: Introductionsupporting
confidence: 77%
“…On the other hand, some surface processing methods are hot working ways, such as laser processing, in which melting and recrystallisation will be produced owing to the high temperature during the process. Kietziga et al [18] reported that the femtosecond-lasered sample showed superhydrophilicity after processing and varied to hydrophobic when the sample was exposed to air, which was also observed in our experiment [19]. Therefore, the processing method should be considered in the wetting behaviors transformation study of sealing surfaces.…”
Section: Introductionsupporting
confidence: 77%
“…The clearances between grooves in both transverse and longitudinal directions were the same (a − b). The width of the micro-grooves in both transverse and longitudinal directions was also the same (b), and their depth was set as h. It has been shown that a convex texture can make the surface more hydrophilic [29,30]. It is well known that most solid surfaces carry electrostatic charges, i.e., an electrical surface potential.…”
Section: Electrostatic Analysis Modelmentioning
confidence: 99%
“…[2] Strip grooves with different spacing and width were fabricated on the substrate surface, and the contact angle measured in the parallel direction was 46.1°-71°and 65.2°-94.7°in the vertical direction. [17] Wang et al [18] prepared micro-scale pits and square convex structure on a smooth SiC substrate with an original contact angle of about 91°. The textured surface kept the hydrophilic state after processing, but the contact angle increased with time.…”
Section: Introductionmentioning
confidence: 99%